Essays on economic growth - Vasconcelos, Rafael da Silva (2014)
This dissertation is a conjunction of three essays on the economic growth field. The first essay investigates the existence of resource misallocation in the Brazilian manufacturing sector and measures possible distortions in it. The second essay demonstrate that there is a distinct pattern of structural change between economies and this pattern differs because there are some factors that distort the relative prices and also affect the output productivity. Finally, using a cross-industry cross-country approach, the third essay investigates the existence of an optimal level of competition to enhance economic growth.